Handbook of Stemmatology : History, Methodology, Digital Approaches - Philipp Roelli (De Gruyter, 2020)
Stemmatology studies aspects of textual criticism that use genealogical methods to analyse a set of copies of a text whose autograph has been lost. This handbook is the first to cover the entire field, encompassing both theoretical and practical aspects of traditional as well as modern digital methods and their history. As an art (ars), stemmatology's main goal is editing and thus presenting to the reader a historical text in the most satisfactory way. As a more abstract discipline (scientia), it is interested in the general principles of how texts change in the process of being copied. Thirty eight experts from all of the fields involved have joined forces to write this handbook, whose eight chapters cover material aspects of text traditions, the genesis and methods of traditional'Lachmannian'textual criticism and the objections raised against it, as well as modern digital methods used in the field. The two concluding chapters take a closer look at how this approach towards texts and textual criticism has developed in some disciplines of textual scholarship and compare methods used in other fields that deal with'descent with modification'. The handbook thus serves as an introduction to this interdisciplinary field.